Eficiência de extratos de plantas medicinais e aromáticas em atrair a abelha africanizada (Apis mellifera L.) em cultura de abacateiro (Persea americana Mili.) - Silva, S. R.; Malerbo-Souza, D. T. [UNESP] (My University, 2003)
The objective of the experiment was to test attractive substances for Africanized honey bees, Apis mellifera L., in avocado, Persea americana Mill. Were pulverized extracts of lemon grass (Cympobogon citratus), ocimum (Ocimum sellowii), Lippia alba, orange leaves (Citrus sinensis), eucaliptus leaves (Eucalyptus sp), eugenol and linalol and the frequency of bees on flowers were evaluated. The frequency of honey bees did increase with the application of the extracts falsa melissa, eucaliptus leaves and orange leaves, used as attractants in Quintal variety. The products tested in Eppendorf tubes did not increased the frequency the bees in Quintal and Fortuna varieties.
The efficiency of Medical and Aromatics plants in attracting Africanized honey bees
Keywords: Apis mellifera; Attractants; Avocado; Medicinal and aromatics plants; Persea americana; eugenol; linalool; plant extract; avocado; basil; Cymbopogon citratus; Eucalyptus; honeybee; insect; Lippia; medicinal plant; nonhuman; orange (fruit); plant; plant leaf; Apinae; Apis; Apoidea; Citrus; Citrus limon; Citrus sinensis; Cymbopogon; Insecta; Lippia alba; Melissa; Ocimum; Ocimum basilicum; Persea